Synthesis of polyacrylonitrile/lithium-montmorillonite nanocomposite for solid polymer electrolyte application - Galvan, Mitch-Irene Kate N. (2013)
As a response to the current trend of miniaturization and portability of electronic gadgets, solid polymer electrolytes (SPE) gained much interest for the synthesis of a flexible, light-weight and high performance energy storage device. SPE is a medium through which ions are transported between the anode and cathode. It also served as a separator in the battery.One of the most recent approaches to synthesize SPE is to prepare polymer-clay nanocomposite (PCN). In this study, PCNs were synthesized using Li impregnated MMT (Li-MMT) to promote single-ion conduction; and polyacrylonitrile (PAN) polymer matrix with lower crystallinity to promote ease in ion mobility during conduction. Ion exchange resulted to 4782.5 112.5 ppm Li+ ions present in Li-MMT. The factors affecting ion exchange process were stirring rate, reaction time and LiCl concentration. On the other hand, PAN was plasticized with dimethylformamide (DMF) and propylene carbonate (PC) at various ratios. The effect of combination of plasticizers on the crystallinity of the PAN was determined. It was found that addition of PC causes a higher decrease on the crystallinity of PAN. Measurements of the electrical conductivity of the PCN with 15 wt. Li-MMT and varying amounts of DMF have higher electrical conductivity and the one plasticized with pure DMF exhibited the highest conductivity, which was 3.58x10-8 S/cm. This is possibly due to higher degree of salvation of PAN in DMF since these two have closer solubility parameters.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Solid polymer electrolytes (SPE).; Polymer-clay nanocomposite (PCN).; Polyacrylonitrile (PAN).; Dimethylformamide (DMF).